Corpos da floresta: experiências para resistir - Passos, Yara dos Santos Costa (2019)
The challenge of this thesis was to analyze some representations of the so called, “forest bodies” formed in the Amazon region, and reinvented in other contexts. As Neide Gondim points it out, such experiments start, many times, from stigmas created during the Brazilian colonization process and that, until this day, relapse in various media environment. In addition to Gondim, the theoretical foundation includes authors as Homi Bhabha, who discusses the stereotype notion and the ambivalences of the relations between the colonised and the settler; the anthropologists Eduardo Viveiros de Castro and Manuela Carneiro Cunha, who dedicated themselves to analyze the Amazon communities and the Amerindian perspectivism; also Katz and Greiner, who propose the body-media theory in order to analyze the relationship between body and enviroment. The main question is, how has dance dealt with these media stigmas, and if in testing other ways of perception is able (or not) to break away the colonial cognitive patterns. Beyond the biographies that build the epistemological corpus of the thesis, we selected as empiric corpus, the choreographies “Kuarup or the Matter of the Indian” from Ballet Stagium, “So That the Sky Won’t Fall” from Companhia de Danças Lia Rodrigues, and “Rite of Passage”, “Hybrid Traces” and “AËËË to Talk About What It Wasn’t Lost” from Índios.com Dance Company. The desired result is to contribute with a discussion specifically related to the representations of the bodies of the florest, which almost always revolves around examples of literature, but also to explain the political implications that substantiate broader debates related to the acknowledgement of mechanisms of inclusion to exclusion, as well as many ways of neoliberal capture that deal with the representation of the other from the process of exoticization and objetification